Elevation of neutrophil carcinoembryonic antigen‐related cell adhesion molecule 1 associated with multiple inflammatory mediators was related to different clinical stages in ischemic stroke patients. Issue 7 (3rd June 2022) - Zhang, Yi; Wang, Yijie; Wu, Wei; Liu, Ping; Sun, Shanshan; Hong, Meng; Yuan, Yuan; Xia, Qi; Chen, Zhi
Abstract: Background: We aimed to analyze the level of carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) in neutrophils of ischemic stroke (IS) patients at different stages, together with its roles in neutrophils. Patients and methods: Sixty‐seven patients were classified into acute phase group ( n = 19), subacute phase group ( n = 28), and stable phase group ( n = 20), and 20 healthy individuals who had received physical examination at the same time period as healthy control. We then analyzed the expression level of CEACAM1 and cell viability in CEACAM1 positive and CEACAM1 negative neutrophils by flow cytometry and the content of plasma CEACAM1, neutrophil gelatinase‐associated lipocalin (NGAL), matrix metalloproteinases‐9 (MMP‐9) was measured using enzyme‐linked immunosorbent assay (ELISA), while that of interleukin‐10 (IL‐10) and tumor necrosis factor (TNF) was determined using a Human Enhanced Sensitivity Flex set. Results: Compared with healthy control, the percentage of CEACAM1 positive neutrophils in IS patients showed a significant increase, and a significant increase was also noticed in the content of plasma CEACAM1 at the subacute stage. Reduction in cell viability was observed in CEACAM1 positive neutrophils compared with CEACAM1 negative counterparts. There was a positive correlation between CEACAM1 expression rate in neutrophils and plasma CEACAM1 and IL‐10 content in the subacute group. Compared with acute group and healthy control group, there was an instinct increase in the level of plasma MMP‐9 and NGAL in subacute group. Conclusions: Our data showed that there was a rapid increase of CEACAM1 in neutrophils at the acute stage of IS. We speculated that CEACAM1 may serve as an inhibitory regulator involving in the progression of IS. Abstract : Ischemic stroke is associated with several factors. This study aims to analyze the level of carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) in neutrophils at different stages of ischemic stroke (IS), together with the roles of CEACAM1 on neutrophils. Our data showed that there was rapid elevation of CEACAM1 in the neutrophils at the acute stage of IS. Reduction of cell viability was observed in CEACAM1 positive neutrophils compared to CEACAM1 negative counterparts. Moreover there was a positive correlation between CEACAM1 expression rate in the neutrophils and plasma CEACAM1 and IL‐10 content in the subacute group. We speculated that CEACAM1 may serve as an inhibitory regulator involving in the progression of IS.